Modern Medicines (Assortment) and Trends in the Improvement of Dosage Forms of Hepatoprotective Agents (Review) - D. A. Petrukhina; I. V. Pletneva; B. B. Sysuev (Разработка и регистрация лекарственных средств)
Introduction. Liver diseases with all the variety of clinical manifestations have common pathogenetic links at the cellular level. The group of hepatoprotective agents is represented by drugs that exhibit versatile mechanisms for protecting liver cells from the effects of damaging factors, the main of which are membrane-stabilizing, antioxidant, regenerative, detoxifying, choleretic and anti-inflammatory effects. The high therapeutic and hepatoprotective effectiveness of modern drugs is largely due to their metabolic effects, as well as their ability to bind free radicals and reactive oxygen species in the cell.Text. The purpose of this work is to form an analytical review of the literature on the assortment and concepts of improving the dosage forms of hepatoprotective agents. According to the analysis and systematization of modern publications devoted to the use of hepatoprotectors in the treatment of liver diseases, it is shown that it is necessary to develop new formulations and combinations of biologically active substances with the manifestation of versatile mechanisms of hepatoprotection, as well as to improve the composition and manufacturing technologies of existing traditional therapies. One of the current trends is the use of new substances in the development of traditional and innovative dosage forms. The search for biologically active molecules with antioxidant, antiradical and membrane-stabilizing activity that can be considered as effective hepatoprotectors continues. An integral task of pharmaceutical development is the creation of bioavailable drugs that have a prolonged effect and minimal side effects. A promising direction in pharmaceutical technology is the development of innovative drugs for the directed transport of biologically active molecules to the affected organ.Conclusion. As a result of the analysis of modern data, priority directions for the development and improvement of existing formulations based on modern approaches to the production of innovative dosage forms are identified. The relevance of improving the dosage forms of hepatoprotectors presented on the pharmaceutical market is shown. Of particular interest is the development of innovative targeted delivery systems with effective and safe hepatoprotectors in various combinations, including those based on cinnamic acid derivatives.